Relationship between intensity of physical activity and health-related quality of life in Portuguese institutionalized elderly - lobo, a (2008)
Health-related quality of life (HRQOL) is considered to be the key goal for health promotion in older people. This study explores the relationship between HRQOL and objectively measured intensity of physical activity (PA) in institutionalized older adults. The analysis of the PA patterns of the subjects in relation to recommended levels of PA was also performed. One hundred and eighty-five residents of long-term care homes aged 65 years or more, volunteered for this study. The Medical Outcome Study Short Form 36-Item health survey (MOS SF-36) questionnaires and the uni-axial MTI Actigraph were used to assess HRQOL and PA, respectively. Participants were classified as less active, reasonably active and more active by tertile of moderated physical activity (MPA). (i) The men represented a greater number of counts/h and min of MPA in all the tertile groups; (ii) men from the less active group had a significantly higher body mass index; (iii) women came third and exhibited less total activity even though they used this time in more intense activities; (iv) there was a higher significant correlation between MPA, physical function and negative association with body pain in relation to the time of institutionalization in both sexes but was more strongly visible in men; and (v) only men presented a significant positive association with physical health, mental health and vitality. Any intensity of PA seems to be better than no activity for HRQOL, but MPA confers greater benefits for the perception of physical function and body pain in the case of institutionalized elderly persons.